Opportunities and Challenges of Islamic Economics in Empowering Agrarian Communities - Agrisa Ditama, Rezki; Syukrawati, Syukrawati; Nilda, Elvi; Mursal, Mursal (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2024)
Ideally, the application of Islamic economics in empowering the agrarian community in Kerinci Regency could provide significant opportunities to improve farmers' welfare through Sharia principles such as profit-sharing and fair rental systems. However, the reality on the ground reveals several challenges, including a lack of understanding of Islamic economics, limited access to modern technology, and issues in capital management and market access. This study aims to explore the opportunities and challenges of Islamic economics in the context of agrarian empowerment in Kerinci Regency and to provide strategic recommendations to address these obstacles. This article falls under field research with a qualitative approach, utilizing a case study method. The research concludes that, despite its challenges, consistent application of Islamic economic principles can enhance productivity and welfare for farmers and positively impact the mechanisms of agrarian empowerment in accordance with Islamic economic principles.